FILSAFAT PENDIDIKAN KI HADJAR DEWANTARA DAN SUMBANGANNYA BAGI PENDIDIKAN INDONESIA - Suparlan, Henricus (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2015)
Globalization is influenced by fundamentalist spirit of the market has resulted in education is not fully regarded as an effort to educate the nation and the liberation of man, but began to shift toward education as a commodity. To counteract this kind of educational model, the concepts of Ki Hadjar Dewantara education is offered as a solution to the distortions implementation of education in Indonesia today. According to Ki Hadjar Dewantara, the essence of education is to incorporate culture in the child, and put the child into the culture so that children become human beings. Educational philosophy Ki Hadjar Dewantara Among these so-called philosophy of education in which the convergence of the philosophy of progressivism about the child's natural ability to resolve the problems faced by giving the widest freedom of thought, but it also uses culture that has stood the test of time, according to essentialism, as the basic education of the child to achieve his goal. In this case Ki Hadjar Dewantara using native Indonesian culture while the values of the West are taken in accordance with the theory of selective adaptative Trikon (continuity, convergent and concentric). Three contributions of Ki Hadjar Dewantara’s educational philosophy for the Indonesian education are the application of a trilogy of leadership in education, three centers of education and the paguron system.